IMPLEMENTASI EKSTRAKURIKULER JUZ’AN USBU’AN DALAM UPAYA MEMBENTENGI SISWA DI ERA REVOLUSI INDUSTRI 4.0 (Studi Kasus di MA Sunan Prawoto Pati) - Afif Takhlishi (PASCASARJANA UNISNU, 2019)
AbstractThis study aims to describe the implementation of juz'an usbu'an extracurricular activities in an effort to fortify students in the era of the industrial revolution 4.0. This research is a qualitative research using a case study type. The research was conducted at MA Sunan Prawoto Pati. From the research results, it can be found that in an effort to fortify students from the negative impacts of the industrial revolution 4.0 MA Sunan Prawoto Pati uses information technology (in this case WhatsApp social media) for positive things, one of which is tadarus Al-Qur'an through the WA group. . Another goal of these activities is none other than the cultivation of character and enforcement of the potential souls of students so that they are filled with positive things as a provision for life in the future.Keywords: extracurricular; era of industrial revolution 4.0; effort to fortify students